2018
DOI: 10.1186/s12913-018-3006-0
|View full text |Cite
|
Sign up to set email alerts
|

Geographic assessment of access to health care in patients with cardiovascular disease in South Africa

Abstract: BackgroundNoncommunicable diseases (NCDs) including cardiovascular diseases (CVDs), diabetes, cancer and chronic lung disease are increasingly emerging as major contributors to morbidity and mortality in developing countries. For example, in South Africa, 195 people died per day between 1997 and 2004 from CVDs related causes. Access to efficient and effective health facility and care is an important contributing factor to overall population health and addressing prognosis, care and management CVD disease burde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Concerning residence, the current study showed that more than half of studied patients were from rural areas, this may be due to lack of health care provided, take more time to diagnosed, and low educational level in rural area. This result was in the same line with Kapwata & Manda, (2018) ) (21) who found that, when increase distance from health care facilities, the cardiovascular disease was increased and morbidity and mortality also worsen. Moreover our findings were in the same line with another study conducted by Amaal F et al, ( 2017) ) (19) who revealed that majority of the studied patients were from rural area.…”
Section: Regarding To Demographicsupporting
confidence: 89%
“…Concerning residence, the current study showed that more than half of studied patients were from rural areas, this may be due to lack of health care provided, take more time to diagnosed, and low educational level in rural area. This result was in the same line with Kapwata & Manda, (2018) ) (21) who found that, when increase distance from health care facilities, the cardiovascular disease was increased and morbidity and mortality also worsen. Moreover our findings were in the same line with another study conducted by Amaal F et al, ( 2017) ) (19) who revealed that majority of the studied patients were from rural area.…”
Section: Regarding To Demographicsupporting
confidence: 89%
“…Second, in addition to lack of stroke registries, hospital-based data often may be inadequate to estimate incident cases due in part to unknown denominator or population at risk. Under-representation of cases could also be due to poor access to hospital services often related to distance and out-of-pocket costs for stroke services and care (39,40). Third, although hospital-based studies are relatively preferred in the absence of stroke registry to investigate stroke incidence (34,41), there were however insufficient information from most hospital-based studies to understand if these estimates were recurrent or first-ever strokes.…”
Section: Discussionmentioning
confidence: 99%
“…Vehicle routing was determined using an ArcGIS Network Analyst tool , which optimized a set of transport routes to reach the set coverage targets, taking into account expected sample volumes, distance from the viral load laboratory, or transport hub to the facility, actual drive times and practical service delivery constraints (i.e. maximum kilometres driven in a day, working hours of a driver).…”
Section: Methodsmentioning
confidence: 99%